Loss, Desire, and Wisdom in Nostalgia Narrative of Willa Cather’s The Professor’s House - Bruce Dame Laoera (J-Lalite: Journal of English Studies, 2023)
Scholarship fields, especially in history and memory studies, have broadly utilized the notion of nostalgia. It has also become an essential part of understanding the narrative in literature. Some studies have used nostalgia and memory to analyze novels. From a qualitative approach, this study analyzes two intrinsic elements (settings and characters) in The Professor’s House, written by Willa Cather. It applies the nostalgia concept as the main framework. Here, it provides a narrative discussion about people and nostalgia that symbolize loss, desire, materialism, and wisdom